Citation as a Basis for Differentiating Mass Media Genres - E. A. Nikonova (Научный диалог)
Citation is considered as a tool for genre differentiation of mass media texts. A qualitative and quantitative analysis of citation in the genres of “news report”, “analytical article” and “opinion” was carried out, which are texts with varying degrees of representation of the author’s assessment, which can be expressed, including by citation. A system of parameters has been developed, on the basis of which it would be possible to carry out genre differentiation of newspaper texts. It includes quotations, the type of verb introducing the quotation, the presence and nature of the additional construction, and the source of the quotation. The data obtained indicate that the analytical article is dominated by direct quotations introduced by neutral verbs. It is noted that official sources are most often used as a source of information, this corresponds to the genre’s desire for objectivity and impartiality. It is shown that in the genre of “opinion” quotations as interspersed with someone else’s text are rare; citation mainly performs evaluative and expressive functions, which is confirmed by a high percentage of segmented citations, as well as the prevalence of such sources of information as the collective and the media. It was revealed that citation in a news message meets such genre requirements as compressed volume, information compression and generalization.